2021
DOI: 10.7869/djo.659
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Profile of Ocular Trauma in A Mid-Zonal Hospital of Armed Forces in North-East Region of India

Abstract: Introduction: ocular trauma is an important cause of preventable ocular morbidity and blindness in addition to socioeconomic and psychological ramifications.The spectrum of ocular trauma ranges from minor injuries to very severe sight threatening injuries. Trauma is inevitable in war zone and routine army exercises.There are very few studies establishing relationship between occupation and ocular trauma in armed forces. This study was conducted to provide us with epidemiological data on ocular trauma cases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…The Indian data on ocular injuries during war is scarce, with very few studies documenting the incidence and pattern. [ 16 17 ] Our study showed that out of all the injuries impacting the globe, OGIs were predominant and formed nearly half of the reported injuries. Similar to our study, Thach et al .…”
Section: Discussionmentioning
confidence: 80%
“…The Indian data on ocular injuries during war is scarce, with very few studies documenting the incidence and pattern. [ 16 17 ] Our study showed that out of all the injuries impacting the globe, OGIs were predominant and formed nearly half of the reported injuries. Similar to our study, Thach et al .…”
Section: Discussionmentioning
confidence: 80%